The natural A3B3 reassortant of the infectious bursal disease virus (IBDV) in Vietnam detected in 2011 through phylogenomic and sequence analyses - Thi Roan, Do; Kim Xuyen, Le Thi; Thanh Huong, Doan Thi; Thi Khue, Nguyen; Khanh Linh, Pham Thi; Hoa, Le Thanh (Vietnam Journal of Biotechnology, 2023)
Infectious bursal disease, also known as Gumboro disease, is a persistent infection that causes severe economic losses in poultry worldwide. The causative agent, infectious bursal disease virus (IBDV), is an immunosuppressive pathogen that frequently mutated and reassorted, generating various genotypes during its evolution. The bi-segmented IBDVs of serotype 1 were divided into four phenotypes (cIBDV, varIBDV, vvIBDV, and aIBDV) and classified into seven genogroups (G1–G7) based on segment A, and A1–A8 and B1–B5 on both segments A and B, respectively. Besides, there have been reassortants which were detected among the naturally existing IBDV population. The phylogenomic and sequence analyses showed that the strain (GKNT)2011-Vietnam (MK544935) represents genotype A3B3, whose segment A was derived from “very virulent” strains (A3 = very virulent-like, vvIBDV), while segment B was from the early Australian-like genogroup (B3 = early Australian-like). The maximum likelihood (ML) tree from the 64 VP0 sequence-based phylogenetic analysis (segment A) showed that the GKNT, together with the other three Vietnamese (G202, GHUT-12, and BDG23) strains, was placed into the A3 genogroup, while the VP1 analysis grouped its segment B with the ancestor (002-73)1973-Australia-B3A7 (M19336) of the early Australian-like B3 genogroup. The B3 subclade of the Vietnamese GKNT and Australian 002-73 strains was placed as a sister to a subgroup encompassing two strains, one from China (AY705393-(Gx)1996-China-B3A3), and one strain from Venezuela (AJ880090-(02015.1)2002-Venezuela-B3A3). Other strains from China (JX134486-(GX-NN-L)2011-China-B3A3 and GQ451331-(HLJ-0504)2005-China-B3A3) were found in a paraphyletic subgroup distinct from the aforementioned strains. The Vietnamese GKNT reassortant has five genotypical amino acids, 222A, 153Q, 256I, 294I, and 299S, in VP2, which are characteristics of the G3a very virulent or A3 genotype and also seen in VP2 of the A3-reference vvIBDV strains, D6948 and 89163. Only one amino acid (990V) in VP3 was found to be different from that of the two vvIBDV (D6948 and 89163). Regarding segment B, the GKNT VP1 differed from the 002-73 Australian ancestor strain (B3 genotype) at only three sites (K13T, N511S, and T576A). The profile of evolutionary distances in segment A indicated the relationships between the (GKNT)2011-Vietnam and some of the Chinese and global groups. The genogrouping results from the GKNT strain for the first time provide the genetic datasets of the constellation of reassortant A3B3 genogroups and contribute to the understanding of the emerging evolutionary lineages of IBDVs in Vietnam and worldwide.